PHARMACEUTICAL CARE OF ADOLESCENTS WITH DIABETES MELLITUS TYPE 1: THE DIADEMA STUDY, A RANDOMIZED CONTROLLED TRIAL. Issue 1 (14th December 2015) - Obarčanin, Emina; Krueger, Manfred; Mueller, Petra; Nemitz, Verena; Schwender, Holger; Hasanbegović, Sniježana; Kalajdzisalihovic, Sena; Läer, Stephanie
Abstract : Background: Adolescents with type 1 diabetes mellitus (T1DM) often show low adherence to complex insulin regimens, leading to poor glycemic control. The benefit of pharmaceutical care in adults with diabetes mellitus type 2 (T2DM) has been widely explored; however, evidence in adolescents with T1DM remains scarce. Objective: To evaluate the impact of pharmaceutical care in adolescents with T1DM provided by a multidisciplinary team on multiple important clinical outcomes. Setting: At the outpatient Helios Paediatric Clinic and at the 12 regular community pharmacies of the study patients with 14 pharmacists in the Krefeld area, Germany, and at the University Pediatric Clinic with one pharmacist on-site in Sarajevo, Bosnia-Herzegovina. Methods: A randomized, controlled, prospective, multicenter study in 68 adolescents with T1DM. The intervention group received monthly structured pharmaceutical care delivered by pharmacists plus supplementary phone calls for 6 months. The control group received usual diabetic care. Data were collected at baseline and after 3 and 6 months. In addition, HbA1c was measured after 12 months. Main outcome measures The between-group difference in the change from baseline in glycosylated hemoglobin (HbA1c), the number of severe hypoglycemic events in both groups, and patient well-being in the intervention group. Results: The improvement from baseline in HbA1c was significantly greater in the intervention group than in the control group after 6 months (change from baseline −0.54 vs. +0.32%, p=0.0075), even after adjustment for country-specific variables (p=0.0078). However, the effect was more pronounced after only 3 months (−1.09 vs. +0.23%, p=0.00002). There was no significant between-group difference in the number of severe hypoglycemia events. After 6 months, the well-being according to the WHO-5 index in the intervention group increased significantly from 52.8% to 63.3%. After 12 months the mean total HbA1c remained significantly reduced in the intervention compared to the control group (8.6% vs. 9.5%, p=0.0184). Conclusion: The improved outcomes seen in this study provide new evidence that pharmaceutical care adds value to the management of T1DM in adolescents. However, the optimal methods of achieving sustained long-term improvements in this specific patient population require further study.